Attitudes of Secondary School Science Teachers toward Teaching Diverse Students - Iva Nandya Atika; Norimune Kawai; Atsuhiko Funabashi (INKLUSI, 2021)
Teachers’ attitudes are crucial to promote inclusive science practices, including those with special educational needs (SEN). This study aimed to investigate science teachers’ attitudes toward teaching diverse student and to identify the elements that may influence teachers in a positive manner toward including SEN students in science classrooms. 202 science teachers in the Banjarnegara Regency, Indonesia participate this study. A survey was conducted and analyzed by a three-way ANOVA test to know the relationship among teachers’ variables and their attitudes toward teaching diverse student groups. The results suggested that 71.8% teachers have moderately positive attitudes concerning teaching diverse student groups in general education classrooms. There were no statistically significant interaction effects among teachers’ variables. Teachers’ personal experiences in interacting with SEN students were found to be the main effect that contributes teachers in acquiring positive attitudes toward involving SEN students in regular classrooms (p < 0.01). Sikap guru sangat penting untuk mendukung praktik pembelajaran IPA yang inklusif, termasuk pada Anak Berkebutuhan Khusus (ABK). Penelitian ini bertujuan untuk menyelidiki sikap guru IPA dalam menghadapi peserta didik yang beragam dan mengidentifikasi faktor-faktor yang mempengaruhi secara positif sikap guru IPA dalam mengikutsertakan ABK pada pembelajaran IPA. Survei dilakukan pada 202 guru IPA di Kabupaten Banjarnegara, Indonesia menggunakan kuisioner ATTDS dan dianalisis dengan tes ANOVA tiga arah untuk mengetahui hubungan antara variable guru IPA yang diteliti dan sikap guru IPA terhadap pembelajaran di kelas. Hasil survei menunjukkan bahwa 71,8% guru IPA memiliki sikap yang cukup positif terhadap seluruh skala ATTDS. Secara statistik tidak ditemukan efek interaksi yang signifikan antara ketiga variabel. Pengalaman guru IPA berinteraksi dengan ABK ditemukan sebagai aspek utama yang memberikan konstibusi signifikan pada perbedaan sikap guru IPA dalam memperoleh sikap positif untuk melibatkan ABK di kelas IPA reguler (p<0,01).